Analisi combinata di dati morfologici e molecolari per lo studio degli artropodi terrestri dell'Antartide - Antonio Carapelli; Claudia Brunetti; Claudio Cucini; Chiara Leo; Francesco Nardi; Pietro Paolo Fanciulli (2021)
Combined analysis of morphological and molecular data for the study of the terrestrial arthropods of Antarctica The terrestrial fauna of Antarctic invertebrates is the subject of growing interest in discovering how life interacts with the polar environment and how millions of years of evolution have shaped its biodiversity. Classical taxonomic approaches, complemented by molecular tools, are improving our understanding on the systematic relationships between species, changing the nomenclature of some taxa and challenging the taxonomic status of others. Furthermore, profiles of gene expression of mites and springtails and the study of their associated microbiome could represent additional tools for understanding the mechanisms of resistance of the endemic species of Antarctica in the light of recent global climate changes.